(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
A fascinating web of history, art, and community, cultural tourism is a powerful trend that is changing the way people travel all around the globe. Through the prism of cultural discovery, this study delves into the life-altering potential of travel to forge a profound connection with the many cultures and histories that make up our planet. Immersive interactions abound in culturally rich destinations, from the lively alleys of old towns to the tranquil landscapes resonating with stories of the past. Cultural tourism invites visitors to become more than simply onlookers; they are invited to become active players in the stories of our collective history.